De-bundled single-walled carbon nanotube-modified sensors for simultaneous differential pulse voltammetric determination of ascorbic acid, dopamine, and uric acid. (22nd January 2018) - Thirumalai, Dinakaran; Subramani, Devaraju; Yoon, Jang-Hee; Lee, Jaewon; Paik, Hyun-jong; Chang, Seung-Cheol
Abstract : De-bundled SWCNTs modified glassy carbon electrode for the simultaneous differential pulse voltammetric determination of ascorbic acid, dopamine, and uric acid. Abstract : A new approach based on differential pulse voltammetry (DPV) was developed for the simultaneous determination of ascorbic acid (AA), dopamine (DA), and uric acid (UA) using a modified glassy carbon electrode (GCE). The sensor was constructed by a simple "one-step" technique, wherein de-bundled single-walled carbon nanotubes (SWCNTs) were drop-cast onto the GCE. Without de-bundling, the SWCNTs were poorly dispersed in aqueous solution and were ineffective for the one-step procedure. De-bundling of the SWCNTs was achieved using a small amount (0.1 wt%) of the synthesized polymer dispersant, sulfonated poly(ether sulfone) (SPES); the de-bundled SWCNTs had a high aspect ratio (length = 2.5 ± 1.0 μm; height = 2 ± 1 nm, as determined using transmission electron microscopy and atomic force microscopy). The de-bundled SWCNTs also led to enhanced electrocatalytic activity and selectivity of the modified sensor for the simultaneous determination of AA, DA, and UA in DPV measurements: the peak-to-peak separation values were 221, 119, and 340 mV ( vs. Ag/AgCl) for DA–AA, UA–DA, and AA–UA, respectively. The dynamic linear ranges for AA, DA, and UA were 0.2–1.6 mM, 5.0–50 μM, and 5.0–60 μM, and the detection limits were 10.6 μM, 15 nM, and 113 nM (S/N = 3), respectively. The analytical performance of the developed sensor was demonstrated in the determination of AA and DA in commercial pharmaceutical samples (vitamin C tablets and DA injection). The characteristics of the modified sensor make it promising for the individual or simultaneous determination of AA, DA, and UA.